Remote Control and Administration of Computer Network via SMS - Gupta, Prerana; Pagar, Mayuri; Patil, Gaurav Patil; Ugale, Rahul (International Journal of Computer Sciences and Engineering, 2014)
The administrators are always worried about not being informed of the failure which takes place in network, or they are informed lately. Even if they are informed soon, it is not possible for them to reach the location to solve the problem. This mainly occurs because the network manager needs to go there or need an access to internet to fix the problem. This paper suggests a method for remote administration of computer network. Also network managers can send commands to the application software by Short Message Service (SMS) to let it issue commands for fixing the failure. By applying this approach, network managers can control and manage their network when they are far from the network location. In this approach administrator can send an SMS and get all the information what exactly is client doing.